IMPROVING BEGINNING CALCULATING ABILITY THROUGH MODIFIED COGGLAK MEDIA IN CHILDREN AGED 4-5 YEARS - Pratistiningtyas, Mittha; Rakhmawati, Nur Ika Sari (Golden Age: Jurnal Pendidikan Anak Usia Dini, 2023)
Researchers will conduct this research aiming to improve the numeracy skills of children aged 4-5 years through the media of saving corn at Pembina II Sooko Public Kindergarten, Mojokerto. This study used the Classroom Action Research (CAR) method which was carried out using two cycles of action. The subjects of this study were 26 children from Group A1 of TK Negeri Pembina II Sooko. Data collection techniques through observation, interviews, and documentation. The results showed that there was an increase in the numeracy skills of children aged 4-5 years through the "Modified Congklak" media. The results obtained in Cycle I were 30.8% due to several causal factors, namely the child was still confused if the number taken was 5 but the corn that was put into the glass cup was less than 5. So in Cycle II it is hoped that it can be followed up by motivating children through stories and giving rewards, training children repeatedly, and doing more interesting counting activities. In Cycle II, obtaining 76.9% stated that it had reached an indicator of success. The learning process using Modified Congklak media can improve the numeracy skills of children aged 4-5 years. Thus it can be concluded that through Modified Congklak media it can improve numeracy skills in group A1 children at Pembina II Sooko Public Kindergarten.